Handwritten Signature Verification: New Advancements and Open Issues - Impedovo, D.; Pirlo, G.; Plamondon, R. (2012 International Conference on Frontiers in Handwriting Recognition, 2012)
Recently, research in handwritten signature verification has been considered with renewed interest. In fact, in the age of e-society, handwritten signature still represents an extraordinary means for personal verification and the possibility of using automatic signature verification in a range of applications is becoming a reality. This paper focuses on some of the most remarkable aspects the field and highlights some recent research directions. A list of selected publications is also provided for interested researchers.